ANKLE BRACE USE AND RISK OF ACUTE LOWER EXTREMITY INJURY AMONG FEMALE HIGH SCHOOL VOLLEYBALL PLAYERS. Issue 4 (28th April 2020) - Kliethermes, Stephanie; McGuine, Timothy; Biese, Kevin; Bell, David; Watson, Andrew; Brooks, M. Alison; Post, Eric; Lang, Pamela
Background: Lower extremity injuries (LEIs), particularly ankle sprains, are the most common injury reported among female volleyball players. Many athletes wear ankle braces to help prevent injury; however, it is unknown whether ankle brace use reduces the rate and severity of ankle and LEI in these athletes. Hypothesis/Purpose: Determine if ankle brace use is associated with a reduced rate and severity of LEIs and ankle injuries among female high school volleyball players. Methods: 2073 female volleyball players from 78 high schools were prospectively followed for injury, including acute LEI, during their fall 2018 volleyball season. Baseline data was collected on each participant including ankle brace use and type worn. Brace type was classified as soft- (e.g. fabric) or hard-shell. Injury severity was measured as days lost from sport. Incidence rates are reported per 1000 athlete exposures. Results: 210 acute LEIs were observed during the season, of which 122 (58%) were ankle injuries. 76% of non-contact LEIs were due to jumping/landing or rotating around a planted foot. Similarly, 76% of contact LEIs were due to the floor or a teammate. The rate of LEI for athletes wearing soft-shell(SS) braces was 1.14 (95% CI: 0.76, 1.72), compared to 0.53 (95% CI: 0.25, 1.10) for those wearing hard-shells (HS) and 0.52 (95% CI: 0.37, 0.71) for those not wearing braces (NONE). The rate of a LEI for athletes wearing SS was 2.22 (95% CI: 1.31, 3.74) times as high as that for NONE (p=0.003). No association was found between LEI risk in athletes wearing HS versus NONE (IRR: 1.02, 95% CI: 0.45, 2.30). Similarly, the rates of ankle injury for HS, SS and NONE were 0.08 (95% CI: 0.01, 0.530), 0.40 (95% CI: 0.20, 0.79), and 0.16 (95% CI: 0.09, 0.28), respectively. The rate of ankle injury was 2.5 times as great in participants wearing SS compared to NONE (p=0.04). No association was detected for HS braces (p=0.48). No difference in median days lost for LEI (HS: 2[IQR 1, 13], SS: 4[1, 10] None: 3[1, 9]) or ankle injury (HS: 7[IQR 2, 13], SS: 5[1, 11] None: 3[1, 10]) was detected by brace use (p=0.99, p=0.79, respectively). Conclusion: The use of SS braces resulted in an increased risk of LEI and ankle injury among female high-school volleyball players; moreover, HS braces were not found to be associated with injury risk nor did ankle brace use affect severity of LEI and ankle injury in this population.